The Cambridge handbook of social representations - Sammut, Gordon; Andreouli, Eleni; Gaskell, George; Valsiner, Jaan (Cambridge, [England] : Cambridge University Press, 2015)
"A social representations approach offers an empirical utility for addressing myriad social concerns such as social order, ecological sustainability, national identity, racism, religious communities, the public understanding of science, health and social marketing. The core aspects of social representations theory have been debated over many years and some still remain widely misunderstood. This handbook provides an overview of these core aspects and brings together theoretical strands and developments in the theory, some of which have become pillars in the social sciences in their own right. Academics and students in the social sciences working with concepts and methods such as social identity, discursive psychology, positioning theory, semiotics, attitudes, risk perception and social values will find this an invaluable resource."--Back cover.
Part I. Foundations. 1. Social representations: a revolutionary paradigm? / Gordon Sammut, Eleni Andreouli, George Gaskell and Jaan Valsiner -- 2. Representation in action / Wolfgang Wagner -- 3. Social representations and societal psychology / Claudia Abreu Lopes and George Gaskell -- 4. On (social) representations and the iconoclastic impetus / Martin W. Bauer -- 5. Researching social representations / Uwe Flick, Juliet Foster and Sabine Caillaud -- Part II. Conceptual developments. 6. Central core theory / Pascal Moliner and Jean-Claude Abric -- 7. Attitudes, social representations and points of view / Gordon Sammut -- 8. Communication and the microgenetic construction of knowledge / Charis Psaltis -- 9. Image, social imaginary and social representations / Angela Arruda -- 10. Collective remembering as a process of social representation / Brady Wagoner -- 11. Cognitive polyphasia, knowledge encounters and public spheres / Sandra Jovchelovitch and Jacqueline Priego-Hernández -- 12. Making community: diversity, movement and interdependence / Caroline Howarth, Flora Cornish and Alex Gillespie -- Part III. New directions. 13. Social representations and social construction: the evolutionary perspective of installation theory / Saadi Lahlou -- 14. From representations to representing: on social representations and discursive-rhetorical psychology / Stephen Gibson -- 15. Positioning theory and social representations / Rom Harr and Fathali Moghaddam -- 16. Social semiotics and social representations / Giuseppe Veltri -- 17. Identity process theory / Glynis Breakwell -- Part IV. Applications. 18. Representations of world history / James H. Liu and Chris G. Sibley -- 19. Social order and political legitimacy / Christian Staerkl -- 20. Social representations of sustainability: researching time, institution, conflict and communication / Paula Castro -- 21. Social representations of national identity in culturally diverse societies / Eleni Andreouli and Xenia Chryssochoou -- 22. The essentialised refugee: representations of racialized 'Others' / Martha Augoustinos, Scott Hanson-Easey and Clemence Due -- 23. Exploring stability and change through social representations: towards an understanding of religious communities / Mohammad Sartawi -- 24. Of worlds and objects: scientific knowledge and its publics / Nicole Kronberger -- 25. The self-control ethos / Helene Joffe -- 26. Social representations of infectious diseases / Véronique Eicher and Adrian Bangerter -- 27. Social change, social marketing and social representations / Mary Anne Lauri.
Includes bibliographical references (pages 411-470) and index.
Keywords: Social representations